The snared wire technique for Sapien valve implantation in the pulmonary position. Issue 4 (21st May 2020) - Maschietto, Nicola; Sperotto, Francesca; Esch, Jesse E.; Porras, Diego; Callahan, Ryan
Abstract: Objectives: Description of the snared wire technique (SWT) to facilitate the delivery of the Sapien valve in pulmonary position, and comparison with standard delivery technique. Background: Transcatheter pulmonary valve replacement (TPVR) with the Sapien delivery system has proven to be challenging. Therefore, alternative strategies for facilitating its delivery in this position are needed. Methods: Retrospective analysis of patients who underwent TPVR with or without the new SWT. The SWT was chosen as an elective strategy when the anatomy was judged to be challenging for TPVR ( planned SWT ) or as a rescue strategy when a standard delivery failed ( rescue SWT ). Results: From February 2018 to January 2020, 84 patients underwent TPVR with a Sapien S3 valve using either a standard delivery ( n = 63, 75%) or a SWT ( n = 21, 25%). Fifteen patients underwent a planned SWT, six patients underwent a rescue SWT after failure of a standard delivery. All planned SWT cases were successful and, compared to the standard delivery group, no significant differences were found in terms of time to valve‐deployment, fluoroscopy time, procedure time, or frequency of complications. Rescue SWT cases had longer fluoroscopy time ( p = .05), longer time to valve‐deployment ( p = .0001), and higher frequency of complications ( p = .002) including tricuspid valve injury ( p = .0004), but allowed the operator to successfully implant the valve into the desired location. Conclusions: Even in the most challenging anatomies, the SWT represents a feasible and effective alternative strategy for TPVR with the Sapien valve that should be considered when other techniques have failed.